Evaluating the Efficacy of Virtual Reality Distraction Therapy in Reducing Anxiety during Oral Surgery: A Randomized Controlled Trial - Jamal Hameed Alshammarie,; Abdulrahman Odhayb Alanazi,; Noor Mohammed Ashour Aldhafeeri,; Haya Abdulmohsen Alazmi,; Mastorah Abdulmohsen Alazmi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Oral surgery can be a daunting experience for many patients, often accompanied by anxiety and fear. Virtual reality (VR) distraction therapy has emerged as a promising tool to mitigate anxiety in medical procedures. This randomized controlled trial aimed to assess the efficacy and safety of VR distraction therapy in reducing anxiety during oral surgery.